2016
DOI: 10.1161/jaha.116.003760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ethnicity, Age, and Time on Sex Disparities in Long‐Term Cause‐Specific Mortality After Acute Myocardial Infarction

Abstract: BackgroundWe examined the influence of sex, ethnicity, and time on competing cardiovascular and noncardiovascular causes of death following acute myocardial infarction in a multiethnic Asian cohort.Methods and ResultsFor 12 years, we followed a prospective nationwide cohort of 15 151 patients (aged 22–101 years, median age 63 years; 72.3% male; 66.7% Chinese, 19.8% Malay, 13.5% Indian) who were hospitalized for acute myocardial infarction between 2000 and 2005. There were 6463 deaths (4534 cardiovascular, 1929… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a more recent study by Gao et al, ethnic disparities were found to be wider in 30-day and 10-year CV mortality than non-CV mortality in patients with AMI from 2000 to 2005. 25 Our study complements theirs with the inclusion of analyses on incidence and intermediate 1-year mortality.…”
Section: Discussionmentioning
confidence: 84%
“…In a more recent study by Gao et al, ethnic disparities were found to be wider in 30-day and 10-year CV mortality than non-CV mortality in patients with AMI from 2000 to 2005. 25 Our study complements theirs with the inclusion of analyses on incidence and intermediate 1-year mortality.…”
Section: Discussionmentioning
confidence: 84%
“…14 Gao et al suggested that age strongly influenced the association between sex and specific cardiovascular causes of mortality. 15 In the meantime, hemoglobin decline and reduced hematocrit value are the manifestations of anemia, which has high incidence in patients with AMI. 16 In the CADILLAC trial, which evaluated 2082 patients with AMI, approximately 13% of the patients had anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were also significantly higher than a recent large scale study (wherein the 10-year all-cause mortality rate in Chinese AMI patients was 44.7%). 36 …”
Section: Discussionmentioning
confidence: 99%